Avaliação das propriedades nutricionais e sensoriais de snacks de castanha (Castanea sativa Mill.) - Delgado, Teresa (2017)
Aiming to increase the market offer of chestnut based products, for both increased economical return and shelf life, different preservation methods were tested on sliced chestnut. Hot air convective drying, osmotic dehydration, and freeze-drying, followed by both sensorial and chemical analysis (proximate composition, free sugars, organic acids and lipid profiles) during a storage period of up to 60 days were performed. Freeze-dried was the method that better preserved samples freshness, particularly regarding starch and ascorbic, but lipid oxidation after 60 days was higher. Osmotic dehydration followed by oven drying provided the highest sensorial scored samples, with increased lipid protection at expenses of sugar incorporation. In opposition, oven dried samples were less accepted from the sensorial point of view, despite the low composition variability. Along storage, the major variations were observed on the ascorbic acid contents, requiring more effective measures to prevent it. Both freeze-drying and osmotic dehydration followed by hot air convective drying are good methods to reduce chestnut losses associates with its natural perishability, while increasing market offer of healthy snacks.